Organophosphorus-B(C6F5)3 adducts: towards new solid-state emitting materials - Regulska, Elzbieta; Christ, Sonja; Zimmermann, Johannes; Rominger, Frank; Hernandez-Sosa, Gerardo; Romero-Nieto, Carlos (Dalton transactions, 2019)
The coordination of B(C6F5)3 to materials based on six-membered phosphorus heterocycles via PO bonds tunes their physicochemical properties both in solution and in the solid state, remarkably improving their performances in light-emitting layers.